Begonia handibadaganathensis (Begoniaceae), a new species from Western Ghats, India - Aitawade, Makarand Mohanrao; Bachulkar, Madhukar Yallapa; Yadav, Shrirang Ramchandra (Phytotaxa, 2019)
A new species of Begonia, B. handibadaganathensis has been described from the northern Western Ghats of Karnataka. The species differs from all other Indian species of the genus in possessing axillary tubercles, a means of vegetative propagation. Begonia handibadaganathensis is closely allied to B. dipetala but differs mainly in the presence of tubercles in the leaf axils, flower size, stamen number and fruit morphology. The species appears to be a narrow endemic restricted to its type locality.